Ketoasidosis Diabetikum pada Pasien Dewasa Muda dengan Kecurigaan Diabetes Melitus Tipe 2: Laporan Kasus - Shania Alifya Gustri (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2026)
Diabetic ketoacidosis (DKA) is a life-threatening acute metabolic complication of diabetes mellitus characterized by hyperglycemia, metabolic acidosis, and ketosis due to absolute or relative insulin deficiency. DKA may present as the initial manifestation of previously undiagnosed diabetes, particularly in young adults. We report a case of a 27-year-old male who presented with decreased consciousness preceded by shortness of breath. The patient had a three-month history of polyuria, polydipsia, polyphagia, and significant weight loss. Physical examination revealed a Glasgow Coma Scale score of 9 and signs of dehydration. Laboratory findings showed severe hyperglycemia (426 mg/dL), elevated HbA1c (8.5%), leukocytosis, and severe metabolic acidosis (pH 6.8; HCO₃⁻ 5.8 mmol/L). The diagnosis of DKA was established based on clinical and laboratory criteria. Management included aggressive fluid resuscitation, continuous intravenous insulin infusion, electrolyte correction, and antibiotic therapy for suspected infection. The patient showed gradual clinical improvement. This case highlights the importance of early recognition, identification of precipitating factors, and prompt management to reduce morbidity and mortality associated with DKA.